2017
DOI: 10.1002/lsm.22768
|View full text |Cite
|
Sign up to set email alerts
|

Complications from microfocused transcutaneous ultrasound: Case series and review of the literature

Abstract: Background and Objective Microfocused ultrasound (MFUS) technology has been utilized since 2009 for improvement in mild to moderate skin and soft tissue laxity of the face and neck. Few complications have been previously reported, the majority of which include mild and transient erythema, edema, ecchymosis, and nerve paralysis. Rare yet serious potential complications of MFUS for noninvasive skin tightening of the face and neck are, however, possible. Methods & Materials Retrospective multicenter case series o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…The objective of all equipment for non-invasive skin lifting, the microfocused ultrasound one included, consists in heating the specific target tissue by means of a source of energy (focused ultrasound), which at the same time allows avoiding the accompanying damage of the surrounding tissues (1,2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The target tissue is a network of collagencontaining tissues, including the reticular stratum of derma, fibrous septa in subcutaneous fat, and fascial strata.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The objective of all equipment for non-invasive skin lifting, the microfocused ultrasound one included, consists in heating the specific target tissue by means of a source of energy (focused ultrasound), which at the same time allows avoiding the accompanying damage of the surrounding tissues (1,2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The target tissue is a network of collagencontaining tissues, including the reticular stratum of derma, fibrous septa in subcutaneous fat, and fascial strata.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Transcutaneous microfocused ultrasound energy pulses of a short duration of 25-50 msec within the MHz frequency range (to level out any cavitation processes emerging) create precise areas of spatially-focused, chromophoreindependent thermal (60-70 °C) coagulative damage, sized less than 1.0 mm 3 . As a result of this quick spot heating, collagen fibers degrade, and this destroyed collagen stimulates neocollagenesis by the "feedback" principle, increasing the thickness of derma and the collagen content in its reticular stratum further on, (1,2,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important that the clinician be aware of the risks of any procedure that he/she performs and the knowledge to minimize such risks. Friedmann et al have reported on complications from microfocused transcutaneous ultrasound including blistering, erosion, atrophy and cutaneous necrosis. The authors speculate as to why these complications occurred and make suggestions for minimizing risks.…”
Section: Introductionmentioning
confidence: 99%